2014
DOI: 10.1038/labinvest.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchanger-1 reduces podocyte injury caused by endoplasmic reticulum stress via autophagy activation

Abstract: Podocyte injury has a critical role in the pathogenesis of proteinuria. Induction of endoplasmic reticulum (ER) stress is thought to lead to podocyte injury; however, no effective strategy for reducing ER stress-induced injury has been identified. We investigated specific mechanisms for reducing podocyte injury caused by ER stress. We found that the induction of ER stress in podocytes was related to cytoskeleton injury and increased proteinuria, which was associated with autophagy activation and downregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…In our study, we detected the immunohistochemical expression of SSTR2A in meningiomas with a sensitivity of 89%. This is comparable with the findings detected by Bacchi et al [ 18 ], Agaimy et al [ 19 ] and Menke et al [ 20 ] in their studies that showed sensitivities of 100%, 87% and 100 % respectively. Lower sensitivities of 74% and 63% were stated by Barresi et al [ 21 ] and Durand et al [ 22 ] respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we detected the immunohistochemical expression of SSTR2A in meningiomas with a sensitivity of 89%. This is comparable with the findings detected by Bacchi et al [ 18 ], Agaimy et al [ 19 ] and Menke et al [ 20 ] in their studies that showed sensitivities of 100%, 87% and 100 % respectively. Lower sensitivities of 74% and 63% were stated by Barresi et al [ 21 ] and Durand et al [ 22 ] respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This was statistically highly significant. Bacchi et al [ 18 ] and Menke et al [ 20 ] reported slightly lower specificities of 90% and 88% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sdf4 is a member of the stromal cell derived factor (SDFs) family and functionally classified as a chemokine; SDF-2, SDF-4 and SDF-5 are expressed in mammary tumor tissues and cells and a reduced level of SDF-2, SDF2-L1 and SDF-4 are associated with a poor clinical outcome [ 71 ]. Sodium/hydrogen exchanger 1 (Slc9a1 or NHE-1) is regulator of membrane permeability, sodium ion transport, apoptosis, cell differentiation and growth; it is suppressed during ER stress that causes epithelial injury [ 72 ]. The down-regulation of NHE-1 during chlamydial infection would indicate the induction of ER stress.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that in rats with puromycin aminonucleoside (PAN) nephropathy, the activation of the PI3K/Akt signaling inhibits podocyte apoptosis (20). Furthermore, it has been reported that Na + /H+ exchanger-1 (NHE-1) attenuates podocyte injury via the PI3K/Akt pathway by inducing the activation of autophagy (21). It is thus possible that the PI3K/Akt pathway may be involved in both apoptosis and autophagy during the process of podocyte injury.…”
Section: Introductionmentioning
confidence: 99%